2006
DOI: 10.1016/j.nuclphysb.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Noncritical osp(1|2,R)M-theory matrix model with an arbitrary time-dependent cosmological constant

Abstract: Dimensional reduction of the D = 2 minimal super Yang-Mills to the D = 1 matrix quantum mechanics is shown to double the number of dynamical supersymmetries, from N = 1 to N = 2. We analyze the most general supersymmetric deformations of the latter, in order to construct the noncritical 3D M-theory matrix model on generic supersymmetric backgrounds. It amounts to adding quadratic and linear potentials with arbitrary time dependent coefficients, namely, a cosmological 'constant,' Λ(t), and an electric flux back… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…In particular, the number of deformation parameters in N = 4 type I case is two, while in other cases it is one. For N = 1 + 1 case, the deformation parameters are given by two arbitrary time dependent functions, and accordingly there are infinite number of deformation parameters [3].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the number of deformation parameters in N = 4 type I case is two, while in other cases it is one. For N = 1 + 1 case, the deformation parameters are given by two arbitrary time dependent functions, and accordingly there are infinite number of deformation parameters [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, matrix models with at most quadratic potential, even with arbitrary time dependent coefficients, possess an SO(1, 2) symmetry as Noether symmetry [25].…”
Section: Isometry Of the Background Geometry And Matrix Modelmentioning
confidence: 99%
“…Indeed, in [25] it was shown that matrix models with at most quadratic potential possess so(1, 2) symmetry, and further allow for osp(1|2, R) supersymmetric extension. In Appendix A, we review the SO(1, 2) symmetry and present the explicit form of the transformations.…”
Section: Isometry Of the Background Geometry And Matrix Modelmentioning
confidence: 99%
See 2 more Smart Citations